In Search of Potent 5‐HT6 Receptor Inverse Agonists. (June 2014) - Hostetler, Greg; Dunn, Derek; McKenna, Beth Ann; Kopec, Karla; Chatterjee, Sankar
<x xml:space="preserve">Abstract</x> A series of non‐sulfonamide/non‐sulfone derived potent 5‐HT6 receptor inverse agonists has been disclosed. Representative compound 9 (Ki = 14 nm) displayed selectivity against a set of family members as well as brain permeability 6 h post‐oral administration. In addition, the separated enantiomers of compound 9 displayed difference in activity indicating the influence of chirality on potency.